Bifidobacterium animalis subsp. lactis MN-Gup protects mice against gut microbiota-related obesity and endotoxemia induced by a high fat diet - Niu, Xiaokang; Zhang, Nana; Li, Shusen; Li, Ning; Wang, Ran; Zhang, Qi; He, Jingjing; Sun, Erna; Kang, Xiaohong; Zhan, Jing (Frontiers in Nutrition, 2022)
Obesity has become a public health concern due to its global prevalence and high risk of complications such as endotoxemia. Given the important role of gut microbiota in obesity, probiotics targeting gut microbiota have been developed and applied to alleviate obesity. However, most studies focused on the effects of probiotics on pre-existing obesity, and the preventive effects of probiotics against obesity were rarely studied. This study aimed to investigate the preventive effects of Bifidobacterium animalis subsp. lactis MN-Gup (MN-Gup) and fermented milk containing MN-Gup against high fat diet (HFD)-induced obesity and endotoxemia in C57BL/6J mice. The results showed that MN-Gup, especially the high dose of MN-Gup (1×1010 cfu/kg b.w.), could significantly protect mice against HFD-induced body weight gain, increased fat percentage, dyslipidemia and increased LPS. Fermented milk containing MN-Gup had better preventive effects on fat percentage and dyslipidemia than the fermented milk without MN-Gup, but its overall performance was less effective than MN-Gup. Furthermore, MN-Gup and fermented milk containing MN-Gup could alter HFD-affected gut microbiota and regulate obesity- or endotoxemia- correlated bacteria, which may contribute to the prevention of obesity and endotoxemia. This study revealed that MN-Gup could reduce obesity and endotoxemia under HFD, thereby providing a potential application of MN-Gup on preventing obesity.